2022
DOI: 10.37689/acta-ape/2022ao0310345
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade a vivenciar uma gravidez não intencional entre mulheres usuárias do Sistema Único de Saúde

Abstract: Conflitos de interesse: nada declarar. ResumoObjetivo: Analisar a vulnerabilidade a vivenciar uma gravidez não intencional entre mulheres usuárias de Unidades Básicas de Saúde e os aspectos associados.Métodos: Estudo transversal com 470 mulheres usuárias de Unidades Básicas de Saúde da Coordenadoria Regional de Saúde Leste do município de São Paulo. Os dados foram coletados por meio de entrevistas e utilizou-se regressão logística múltipla para analisar os aspectos associados.Resultados: Aproximadamente metade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…A higher prevalence of MCM use was found in women with two or three or more children compared to those with one or no children. A study conducted in Sao Paulo, Brazil, indicated that women with two or more children considered it important to prevent pregnancy and not to have more children [ 24 ]. These findings are consistent with those of a Peruvian study in which women without children make less use of MCM compared to those who had more than one child [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher prevalence of MCM use was found in women with two or three or more children compared to those with one or no children. A study conducted in Sao Paulo, Brazil, indicated that women with two or more children considered it important to prevent pregnancy and not to have more children [ 24 ]. These findings are consistent with those of a Peruvian study in which women without children make less use of MCM compared to those who had more than one child [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the assessment of inequalities, the variables used were age group (15 to 19 years, 20 to 29 years, 30 to 39, years, and 40 to 49 years) [ 7 , 9 , 20 ]; educational level (up to primary, secondary, higher) [ 6 , 7 ]; currently working (no, yes) [ 21 ]; ethnicity (“non-indigenous” for individuals who self-reported as afro-ecuatorian, white, mestizo, montubio, or others, and “indigenous” for those who self-reported as indigenous) [ 22 , 23 ]; and, area of residence (rural, urban). The following variables were used for the analysis of associated factors: age group (15 to 19 years, 20 to 29 years, 30 to 39, years, and 40 to 49 years) [ 7 , 9 , 20 ]; educational level (up to primary, secondary, higher) [ 21 ]; marital status (married, cohabiting) [ 10 ]; currently working (no, yes); parity (0 to 1, 2, 3 or more children) [ 24 , 25 ]; ethnicity (indigenous, non-indigenous) [ 23 ]; health insurance (yes, no) [ 26 ]; area of residence (rural, urban) [ 7 ]; region of residence (Highlands, Coast, Amazon, Island) [ 13 ]; and wealth quintile (“very poor”, “poor”, “medium”, “rich”, and “very rich”) [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a Brazilian study conducted with 688 women aged 18 to 49 years, approximately 60% intended to become pregnant; in other words, the expectation of women who may complain of post-pregnancy sagging is high. In this scenario, effective and long-lasting methods that require few interventions and high power to activate the endogenous collagen and elastin production cascade are necessary 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that cause tissue sagging are similar to those of aging: atrophy and reduction in epidermal and dermal thickness, fragmentation of elastic fibers, and reduction in the number and function of apocrine glands 10 . The endocrine role in the tissue quality of the abdomen must also be considered because there is a relationship between testosterone and estrogen levels and the amount of collagen altered during pregnancy 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…(Maganha & Melo, 2022) Apesar de o serviço de planejamento familiar ser oferecido no Programa de Saúde da Família (PSF), é sabido que mulheres de minorias étnicas e sociais muitas vezes enfrentam barreiras culturais, bem como desigualdades estruturais que podem impossibilitar o acesso aos serviços de saúde, fazendo com que tenham dificuldade em planejar a gestação. (Costa et al, 2023;Maganha & Melo, 2022).…”
Section: Introductionunclassified